LA GESTIÓN DEL CONOCIMIENTO, FACTOR ESTRATÉGICO PARA EL DESARROLLO - Rodríguez Andino, Milagro (2009)
Management of the knowledge has acquired a meaningful importance as change and development factor in all the occupation of the society. The principal mission of this is to create an environment in the one which the knowledge and the available information in an organization will be accessible and they could be used to stimulate the innovation, to provoke improvements in the decision making and to produce new knowledge, the key is in creating a culture in the one which the information and the knowledge are valued, are shared, are transacted and are used effective and efficiently. The Information Technology and Communications (TIC) have come to provide tools of certain value for the generalization of knowledge bases and constitute a new research and development area in this sense. The work that we present intends to value important aspects to attend between these the policy and the principal elements of the strategy to reach management of the knowledge with the employment of the TIC that permit to impel the development of an organization.